Gestational Risk as a Determining Factor for Cesarean Section according to the Robson Classification Groups - Karina Biaggio Soares; Vanessa Cristina Grolli Klein; José Antônio Reis Ferreira de Lima; Lucas Gadenz; Larissa Emile Paulo; Cristine Kolling Konopka
Abstract Objective To analyze and compare the frequency of cesarean sections and vaginal deliveries through the Robson Classification in pregnant women attended at a tertiary hospital in two different periods. Methods Cross-sectional, retrospective study of birth records, comprising 4,010 women, conducted from January 2014 to December 2015 in the only public regional referral hospital for the care of high- risk pregnancies, located in Southern Brazil. Results The overall cesarean section rate reached 57.5% and the main indication was the existence of a previous uterine cesarean scar. Based on the Robson Classification, groups 5 (26.3%) and 10 (17.4%) were the most frequent ones. In 2015, there was a significant increase in the frequency of groups 1 and 3 (p < 0.001), when compared with the previous year, resulting in an increase in the number of vaginal deliveries (p < 0.0001) and a reduction in cesarean section rates. Conclusion The Robson Classification proved to be a useful tool to identify the profile of parturients and the groups with the highest risk of cesarean sections in different periods in the same service. Thus, it allowsmonitoring in a dynamic way the indications and delivery routes and developing actions to reduce cesarean rates according to the characteristics of the pregnant women attended.